2011
DOI: 10.1093/jmt/48.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Personal Therapy for Undergraduate Music Therapy Students: A Survey of AMTA Program Coordinators

Abstract: The primary purpose of this study was to gather information in order to understand if and how various modalities of personal therapy are employed with undergraduate music therapy students in the United States. AMTA degree program coordinators were asked about 3 therapy modalities, in particular: verbal therapy, music therapy, and expressive arts therapy (excluding music therapy). It was predicted that less than a quarter of the respondents would indicate that personal therapy of any modality was required in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…• Trainees undertaking background reading on personal therapy, with guidance from tutors (e.g., Gardstrom & Jackson, 2011;Murphy et al, 2018;Yalom, 2009).…”
Section: Approaches: An Interdisciplinary Journal Of Music Therapymentioning
confidence: 99%
“…• Trainees undertaking background reading on personal therapy, with guidance from tutors (e.g., Gardstrom & Jackson, 2011;Murphy et al, 2018;Yalom, 2009).…”
Section: Approaches: An Interdisciplinary Journal Of Music Therapymentioning
confidence: 99%
“…In general, there are few empirical attempts to understand the professional development of students trained in art therapy, music therapy or dance movement therapy (Orkibi, 2013). Educational research in the field of music therapy has specifically included focus on the use of musical instruments and musical skills (Kennedy, 2001;Silverman, 2011), supervision (Forinash, 2001;Tanguay, 2008), clinical practice development (Madsen & Kaiser, 1999;Wheeler, 2002), models for self-experiential learning and psychotherapy in education (Gardstrom & Jackson, 2011;Murphy, 2007;Scheiby & Pedersen, 1999), reflexive journaling (Barry & O'Callaghan, 2008) and research on feminist pedagogy in music therapy (Hahna & Schwantes, 2011). Role-play as a form of learning in music therapy education is associated with various domains, such as preparation for practicum placements or in the supervision of practice (Goodman, 2011;Murphy, 2007;Tims, 1989).…”
Section: Role-play In Music Therapy Research and Educationmentioning
confidence: 99%
“…The results of the present study could therefore promote the importance of including personal therapy and experiential learning in Korean music therapy training programs, especially for programs oriented toward a psychodynamic approach. Like Gardstrom and Jackson’s (2011) survey of American Music Therapy Association program coordinators, in which participants shared ethical concerns regarding requiring personal therapy, the present study invites questions regarding the ethicality of requiring personal therapy in Korean music therapy training programs.…”
Section: Limitations and Recommendations For Future Studiesmentioning
confidence: 99%
“…The American Music Therapy Association (AMTA) does not mandate that trainees receive personal therapy as a client, leaving this option up to the directors of individual programs (Jackson and Gardstrom, 2012). Gardstrom and Jackson (2011) reported that most of 41 music therapy directors in their study avoided mandating personal therapy for students, except when students manifested serious personal crises or mental illnesses that interrupted or compromised their training experience. Although multiple studies have emphasized the importance of personal therapy as a client, none examine students’ actual experience of personal therapy as a client.…”
Section: Introductionmentioning
confidence: 99%